Bright Luminous and Stable CsPbBr3@PS Microspheres Prepared via Facile Anti‐solvent Method using CTAB as Double Modifier. Issue 46 (20th July 2020) - Zhou, Juan; Lin, Husitu; Yu, Yingchun; Zuo, Shengli; Li, Baoshan; Liu, Jianjun
Abstract: The past decade has witnessed the increasing interest in cesium lead halide perovskite quantum dots (PQDs) for their excellent optical properties with higher photoluminescence efficiency and tunable emission wavelengths widely applied in white LED, photovoltaic devices, etc. Here we report the preparation of CsPbBr3 PQDs by a facile anti‐solvent method using conventional quaternary ammonium bromide (CTAB) as a double modifier—both proper alkyl group protection and bromine source donator. The as‐formed PQDs are well‐monodispersed cubes with a size of 10–15 nm and high photoluminescence quantum yield (PLQY) of up to 43 %. To enhance the stability of PQDs, CsPbBr3 @PS microspheres were formed by electrospraying process. The microspheres not only show excellent luminous properties, but exhibit much higher stability against air and UV light irradiation due to the super hydrophobic property of polystyrene. Abstract : Bright spots : CsPbX3 (X=Cl, Br, I) perovskite quantum dots (PQDs) have attracted attention recently for optoelectronic applications. Here we illustrate CTAB as a double modifier for capping ligands and additional bromine source to synthesize CTAB‐CsPbBr3 PQDs, which show better stability against air and UV light than OLA‐CsPbBr3 PQDs. We also utilize polystyrene with the super‐hydrophobic property to form CTAB‐CsPbBr3 @PS microspheres by electrospraying process. Therefore, CTAB‐CsPbBr3 @PS microspheres overcome the intrinsic disadvantage of PQDs.